(untitled) (Experimental biology, 2022)
The accumulation of proline in response to the adverse effects of heavy metals on plants has been studied. To elucidate the role of proline in the plant response to stress induced by heavy metal, the effect of this amino acid on the inhibition of nitrate reductase in vitro was studied. The ability of proline to protect NR from the action of zinc, copper, lead and cadmium was found. Other protective mechanisms of heavy metal-induced proline accumulation are also discussed. In addition to antioxidants, compounds called osmoprotectants also play a special role in relieving the negative effects of oxidative stress that occurs in plants. These include glycinbetaine, proline, and mannitol. Among them, the biological role of proline is most common among plants. The results of this study are related to the development of pre-sowing processing (priming) of grains of various varieties of spring wheat to increase its resistance to heavy metals, yield and seed quality. The study is aimed not only at increasing seed germination, growth and development of their seedlings under heavy metal exposure, but also at determining the amount of proline in sprouted seeds after priming. It was carried out under the above-mentioned conditions of different concentrations of priming and copper salt solution and studied how Proline levels change in wheat sprouts. The obtained results show for the first time that the relationship between antioxidants and osmoprotectants changes during oxidative stress caused by heavy metal.